Navigating the ice: Establishing pre-concussion baselines in ice-hockey players for gait assessment utilizing inertial measurement units - Müller, J.; Köppel, N.; Eggenberger, P.; Brunner, E.; Weber, T.; de Bruin, E. D. (Current Issues in Sport Science, 2025)
Introduction Ice hockey can lead to high-energy collisions and traumas and is a sport with high risk of concussion (Ornon et al., 2020). Concussions represent 2-14% of all hockey injuries (Izraelski, 2014). Sports-related concussions (SRC) sustained in professional ice hockey are a common in-competition injury leading to highly individual return to sport that can be associated with symptoms lasting days to months (Höllerer et al., 2023). Following SRC there is an increased risk of subsequent concussion and musculoskeletal injury upon return to play, however, assessments that can detect subclinical changes in function following a concussion are lacking (Dunne et al., 2023). A COSMIN systematic review suggests gait-based assessments using inertial measurement units to capture pre-concussion baseline scores (Dunne et al., 2023). This study measured pre-season pre-concussion gait data in Swiss National League Ice hockey players. Baseline scores will be compared with measures from players sustaining in-season SRC.